Efektivitas Penerapan Literasi Digital terhadap Kecakapan Literasi Siswa Kelas IV SDIT As Salam Tahun Pelajaran 2022/2023 - Deti Nurpadilah; Septian Mukhlis (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2023)
Literacy skills are one of the skills required in the 21st century. This is the background for researchers to see the effectiveness of applying digital literacy to students. The method used in this research is quantitative with a correlation approach. The population in the study were fourth grade students of SDIT As Salam Kampung Simpur Cikarang Selatan, and the research sample amounted to 41 students. Based on the results of data processing, the correlation coefficient between digital literacy and literacy skills is 0.527, meaning that there is a significant correlation between digital literacy and literacy skills. The R2 value is 0.259 which means it shows the contribution of digital literacy variance to the variance of literacy skills by 25.9%.